KAJIAN PENGGUNAAN ISTILAH ILMIAH FISIKA DALAM BAHASA INDONESIA - Nurul Azizah; Aziziah Salsabilah; Fadhilatul Ulya Br Pinem; Nora Lidwina Situmorang; Yosefa T D Situmorang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses the use of scientific physics terms in the Indonesian language and their role in physics learning. The research used a library research method by examining journals, books, and scientific articles related to the topic. The results show that the use of scientific terms in Indonesian helps students understand physics concepts more clearly and systematically. Many physics terms are adapted from foreign languages into Indonesian without changing their scientific meanings. In addition, the development of science and technology also affects the development of physics terminology in Indonesian. Therefore, the use of proper and standard scientific terms is important in supporting scientific communication and physics learning.